Corporate Social Responsibility in Emerging Markets: Case study of the Philippines - Hans, Vanessa Laura (2012)
Corporate Social Responsibility (CSR) is known as the business-society interface (Gond and Matten, 2007). Different definitions of CSR can be found but it is acknowledged that the concept of CSR is strongly influenced by the internal as well as the external environment of each firm. The national business system of the country in which each firm operates is shaping the way CSR is understood, implemented and encouraged (Chapple and Moon, 2005). Those differences involve that each country has its own specificities regarding CSR. This dissertation will focus on the particular case of CSR within emerging nations and will use the Philippines as a case study. Institutional theory will be the basis for this dissertation that aims to investigate the state of CSR in the Philippines.